2004
DOI: 10.2170/jjphysiol.54.465
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Patterns Associated with Trait Anxiety and Breathlessness in Humans

Abstract: During periods of increased anxiety there is an increase in respiratory frequency which correlates significantly with individual trait anxiety. These changes are observed especially in high trait individuals and occur with no change in V . co 2 or tidal volume, but with a resultant decrease in end tidal CO 2 (P ET CO 2 ).Recent work focusing on human brain activities has suggested that the temporal pole and the amygdala in the limbic system are activated during increased anxiety in high-trait individuals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(19 reference statements)
1
16
0
1
Order By: Relevance
“…A previous study tested in healthy subjects reported that anticipatory anxiety increases RR, and that this increase in RR is directly associated with individual anxiety levels 7 . This phenomenon was also observed not only in normal healthy subjects but also in highly anxious patients 16 . In this study, we also found that TTH with high anxiety showed a high increase of RR.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A previous study tested in healthy subjects reported that anticipatory anxiety increases RR, and that this increase in RR is directly associated with individual anxiety levels 7 . This phenomenon was also observed not only in normal healthy subjects but also in highly anxious patients 16 . In this study, we also found that TTH with high anxiety showed a high increase of RR.…”
Section: Discussionsupporting
confidence: 56%
“…In fact, this is the case in many highly anxious individuals, who often exhibit tightness in peripheral muscles. For instance, patients with hyperventilation syndrome often present with chest wall tightness and neck tightness 16 . Stress and anxiety affect muscle tone by increasing gamma-motor input at the muscle spindle, as well as increasing respiration-related muscle activity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those described by other authors, who attributed these changes to pain, fear, and anxiety. 19,20 The perception of the degree of patient anxiety enables the professional to pay attention to stressful situations and adopt measures to minimize anxiety and pain perception during the application of the anesthetic solution. 21 In summary, the inferior alveolar nerve block computer-controlled anesthetic technique provides lower pain intensity as compared with the conventional technique, but does not show statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we assumed that baseline tightness was greater in these children compared with the lower A-Trait group because a significant decrease in RR was observed in the higher anxiety group after one week of RMSG. Chest wall tightness is commonly observed in highly anxious subjects, especially in patients with hyperventilation syndrome 9 . Stress and anxiety enhance muscle tone by increasing intercostal muscle activity through an increase in the gammamotor input at the muscle spindle 9 .…”
Section: Rmsg and Slower Breathingmentioning
confidence: 99%
“…Chest wall tightness is commonly observed in highly anxious subjects, especially in patients with hyperventilation syndrome 9 . Stress and anxiety enhance muscle tone by increasing intercostal muscle activity through an increase in the gammamotor input at the muscle spindle 9 . Our results suggest that RMSG was more effective for children with high trait anxiety.…”
Section: Rmsg and Slower Breathingmentioning
confidence: 99%